Management Of Special Health Services In Islamic Boarding Schools - M. Fakhry Asa Fazary; Sheila Soraya Choliq (The Faculty of Education and Teaching Training, 2023)
Management of special health services at the Nurul Qarnain Islamic Boarding School is a health service activity for students. The aim of this service is to provide physical and spiritual health services for students. The aim of this research is to understand the management of special health services for Islamic boarding schools. This research uses a qualitative approach with data collection methods in the form of interviews, data (document) review and observation. The key informants consisted of one Head of the Health Center and one Postkestren Nurse. For the key informants there were four health section coordinators, seven health section administrators, nine students and one Community Health Center officer. The variables in this research consist of Islamic boarding school development model variables and implementation of special Islamic boarding school health service management. The results of the research show that the implementation of special Islamic boarding school health service management has gone quite well, but several efforts in terms of input, process and output indicators have not been optimally implemented, namely human resources, facilities, health information media, implementation, supervision, evaluation and implementation of health post management. Administrasi Pelayanan Kesehatan Khusus di Pondok Pesantren Nurul Qarnain merupakan kegiatan pelayanan kesehatan kepada santri. Tujuan dari pengabdian ini adalah untuk memberikan pelayanan kesehatan jasmani dan rohani kepada peserta didik. Tujuan penelitian ini adalah untuk mendalami manajemen pelayanan kesehatan khusus pesantren.. Penelitian ini menggunakan pendekatan kualitatif dengan metode pengumpulan data berupa wawancara, telaah data (dokumen), dan observasi.. Informan kunci adalah pengelola puskesmas dan perawat pascakestren. Untuk informan kunci, terdapat empat koordinator dinas kesehatan, tujuh pengurus dinas kesehatan, sembilan mahasiswa, dan satu staf puskesmas.. Variabel penelitian ini meliputi variabel model pengembangan pondok pesantren dan implementasi manajemen khusus pelayanan kesehatan pondok pesantren.. Hasil penelitian menunjukkan bahwa pelaksanaan manajemen khusus pelayanan kesehatan pesantren sudah cukup baik, namun beberapa upaya pada indikator input, proses dan outcome belum berhasil, sektor publik, belum maksimal dikerahkan khususnya sumber daya manusia, fasilitas, sarana informasi medis, pelaksanaan, pengawasan, evaluasi, dan pelaksanaan manajemen layanan khusus kesehatan pesantren.